Pengaruh Harga, Kualitas Pelayanan, Dan Fasilitas Terhadap Daya Minat Pelanggan Minum Kopi Di Coffee Shop Restu Bunda Kota Medan - Ica Putri Andari Banjarnahor; Deni Faisal Mirza (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of this study was to determine how consumer interest in drinking coffee at Coffee Shop Restu Bunda in Medan City is influenced by facilities, service quality, and price. This survey-based study involved sixty clients. The results showed that consumer interest was positively and significantly influenced by price, service quality, and facilities. Coffee Shop Restu Bunda can use this study as a guide to increase consumer interest by improving service standards, providing complete and comfortable facilities, and setting reasonable prices.